Формування підходів до уніфікації понятійно-категоріального апарату інформаційного права - Сопілко, І.М. (Часопис Київського університету права, 2009)
В статье рассматриваются вопросы процесса получения информации органами государственной власти и полномочия органов государства и по получению информации или ее носителей. In the article an author describes the questions of the process of reception of information by state organs and also describes plenary powers of this organs in sphere of receipt of information and its transmitters.